METODE KRITIK MATAN HADIS MISOGINIS MENURUT FATIMAH MERNISSI - Dadah, Dadah (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2018)
Discourse on gender has never been quietly discussed both among academics, politicians, and in peoples daily lives. In the development of the current discussion about gender has involved Islamic thinkers to explore the repertoire of Islamic thought to see the existence of gender discourse in Islam. This condition is inseparable from claims that Islamic teachings are not gender sensitive, and even tend to reduce women, especially when a handful of people talk about the existence of women in the public sphere which is constrained by restrictions on womens movement to gain access in education, social and political fields. Fatimah Mernissi, when analyzing the religious texts already in the yellow book, especially the hadiths of the Prophet. and the narrators who later came up with a new term, namely